AN EVALUATION OF IRANOLOGY CD-ROM DATABASES - Abazari, Zahra; Moghaddam, Alireza Isfandyari; Ghorbabi, Mahboobeh (Malaysian Journal of Library and Information Science, 2017)
This article aims to evaluate Iranology CD-ROM databases using survey method. Data were collected using a researcher-developed checklist which is composed of four main criteria namely storage, search and retrieval, software design, and indexing. The study sampled all Iranology CD-ROMs recorded by the Iranian High Council of Informatics (IHCI). As a result, 35 CD-ROMs were identified for final evaluation. It was found that the most critical point of Iranology CD-ROMs which its defined indices have been less observed by the softwares is related to criterion "search and retrieval", while the most observed indices belonged to criterion "software design". Findings of this study may assist related bodies improve the status of information flow especially in the field of tourism as this resource has a variety of information about different aspects of Iranian history, literature, art and cultural heritage.